Ustāẕulʻulamā : yaʻnī, Ḥaz̤rat Muftī Muḥammad Lut̤fullāh raḥmat Allāh ʻalih kī muḵẖtaṣar savāniḥ ʻumrī - Ḵẖān, Muḥammad Ḥabīburraḥmān, 1867-1950 (SAMP early 20th-century Indian books project ;, 1937)
On the life of Muftī Muḥammad Lut̤fullāh, Indian Islamic scholar.